Are protected areas covering important biodiversity sites? An assessment of the nature protection network in Sicily (Italy). (November 2018) - Signorello, Giovanni; Prato, Carlo; Marzo, Alessia; Ientile, Renzo; Cucuzza, Giuseppe; Sciandrello, Saverio; Martínez-López, Javier; Balbi, Stefano; Villa, Ferdinando
Highlights: Data on 213 vascular plants, and 146 vertebrate fauna, and 81 habitats are used to map areas with high biodiversity value. Spatial analysis shows that only 32% of areas with high biodiversity value are currently protected. A small increment of the existing protected area network could include a disproportionate amount of biodiversity hot spots. Abstract: GIS spatial analysis of three indicators (vegetation value, faunal richness and landscape heterogeneity) was used to detect and map High-Value Biodiversity Areas (HVBAs), estimate the coverage of biodiversity in the Sicilian protected areas network, and identify new priority areas that could improve long-term biodiversity conservation outcomes. Findings indicated that only 32% of HVBAs are currently covered by the protected areas network. Hotspot analysis revealed that a modest expansion (less than 1%) in the current extent of protected areas would include a disproportionate amount (56%) of biodiversity hotspots, and identified prioritized candidates HVBAs for designation of new protected areas.